Influence of power density on high purity 63 mm diameter polycrystalline diamond deposition inside a 2.45 GHz MPCVD reactor. (4th August 2016) - Yu, Shengwang; Wang, Rong; Zheng, Ke; Gao, Jie; Li, Xiaojing; Hei, Hongjun; Liu, Xiaoping; He, Zhiyong; Shen, Yanyan; Tang, Bin
Abstract: 63 mm diameter polycrystalline diamond (PCD) films were synthesized via a microwave plasma chemical vapor deposition (MPCVD) reactor in 99% H2 –1% CH4 atmosphere. Two different conditions, i.e. the typical condition (input power of 5 kW and gas pressure of 13 kPa) and the high power density condition (input power of 10 kW and gas pressure of 18 kPa), were employed for diamond depositions. The color changes of the plasma under the two proposed conditions with and without methane were observed by photographs. Likewise, the concentrations of hydrogen atoms and carbon active chemical species in plasma were analyzed by optical emission spectroscopy (OES). The morphologies and purity of the PCD films were investigated by scanning electron microscopy (SEM) and Raman spectroscopy, respectively. Finally, the transmission spectrum of the polished PCD plates was characterized by a UV–Vis–NIR spectrometer. Experimental results showed that both the concentrations of hydrogen atoms and carbon radicals increased obviously, with the boost input power and higher pressure. The films synthesized under the high power density condition displayed higher purity and more uniform thickness. The growth rates in 10 kW and 18 kPa reached ~7.7 µ m h −1, approximately 6.5 times as much as that occurred in the typical process. Moreover, the polished plates synthesized under the high power density condition possessed a relatively high optical transmittance (~69%), approaching the theoretical values of approximately 71.4% in IR. These results indicate that the purity and growth rate of big-area PCD films could be simultaneously increased with power density.